Pseudo-Oxidation In Lubricants Induced by FAME - Ahbab, Muhammad Nurul; Febriyanto, Luddy; Purwanto, Tri; Abiyoso, Bow; Wikan, Yosua Pribadi (Journal of Mechanical Design and Testing, 2025)
The application of biodiesel in Indonesia is a necessity that in each period experiences an increase in percentage beginning from B2.5, B10, B15, B20, B30 to B35 and even possibly up to B100. The application of biodiesel in all segments, such as shipping, mining, and power plants, has technical issues that are always interesting to be studied by many researchers in the world. This  paper presents an experimental study on the potential for pseudo-oxidation phenomena in lubricants due to biodiesel contamination in lubricants, which is likely to be read as oxidation in FTIR testing. This can occur due to the Fatty Acid Methyl Ester (FAME) content in biodiesel and lubricant oxidation products having identical C=O (carbonyl) groups so that the possibility of wavenumbers detected between FAME and oxidation can influence each other's interpretation. Therefore, experimental studies are essential to simplify the interpretation of used lubricant samples that may be contaminated with biodiesel. By conducting controlled experiments, it becomes easier to distinguish between actual oxidation and the pseudo-oxidation effect caused by biodiesel contamination. This is crucial to ensure accurate condition monitoring and effective maintenance strategies in various industrial applications.